Associations of four important dietary pattern scores, micronutrients with sarcopenia and osteopenia in adults: results from the National Health and Nutrition Examination Survey - Li, Yuan; Gu, Wen; Hao, Wen; Xu, Yadan; Li, Kexin; Zhao, Yueliang; Huang, Qingyun (Frontiers in Nutrition, 2025)
IntroductionWe aimed to comprehensively evaluate the association between four important dietary patterns and micronutrients with sarcopenia and osteopenia. Data were obtained from the National Health and Nutrition Examination Survey 2005-2018.MethodsThe association between dietary patterns and micronutrients with sarcopenia and osteopenia was evaluated by logistic regression models. 6709 and 7161 participants were included in the final analyses.ResultsHigher adherence to HEI-2020, aMed, and DASH dietary patterns was inversely associated with sarcopenia risk, with each standard deviation (SD) increment linked to 18%, 16%, and 14% reductions in odds, respectively. However, DII increased the prevalence of sarcopenia and osteopenia by 44% and 8% per SD increase. Dietary intake of vitamins A, B2, B9, C, calcium, phosphorus, magnesium, copper, and potassium were negatively associated with sarcopenia, whereas vitamins D and K were negatively associated with osteopenia. SIRI and NLR partially mediated the associations among them.DiscussionAdherence to healthy dietary patterns especially anti-inflammatory diet and supplementary micronutrients reduce bone and muscle loss.